2006
DOI: 10.2106/jbjs.d.02924
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Measurements of Torsions in the Tibia and Femur

Abstract: Ultrasound is a viable tool for measuring torsion of the tibia and femur. In order to minimize measurement errors, the ultrasound measurement should be used to calculate the predicted value of torsion with use of the regression equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…We took care to develop a reliable method that accurately measures the amount of torsion in the femur by using validation with dry femora and masking the examiner to the results of MRI. Our ultrasonographic procedures were based on those developed by Hudson et al, 20 with minor modifications made in participant positioning to improve the visualization of the femur. In the study by Hudson et al, 20 participants were seated and semirecumbent, but the examiner in the present study found it difficult to clearly visualize the appropriate anatomical landmarks and read the tilt angle from the inclinometer when that positioning was used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We took care to develop a reliable method that accurately measures the amount of torsion in the femur by using validation with dry femora and masking the examiner to the results of MRI. Our ultrasonographic procedures were based on those developed by Hudson et al, 20 with minor modifications made in participant positioning to improve the visualization of the femur. In the study by Hudson et al, 20 participants were seated and semirecumbent, but the examiner in the present study found it difficult to clearly visualize the appropriate anatomical landmarks and read the tilt angle from the inclinometer when that positioning was used.…”
Section: Discussionmentioning
confidence: 99%
“…Our ultrasonographic procedures were based on those developed by Hudson et al, 20 with minor modifications made in participant positioning to improve the visualization of the femur. In the study by Hudson et al, 20 participants were seated and semirecumbent, but the examiner in the present study found it difficult to clearly visualize the appropriate anatomical landmarks and read the tilt angle from the inclinometer when that positioning was used. Supine positioning of participants allowed better visualization and ease of measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use has been advocated in numerous studies [2,3,7,11,12,25]. Other methods such as MRI [17,18,24] and ultrasound [2,10] also are valid tools for measuring the level of tibial torsion and can be used as reference standards. However, because CT was invented earlier, studies on the validity of MRI and ultrasound have used CT as the reference standard [2,18].…”
Section: Discussionmentioning
confidence: 99%
“…The torsion angle of the tibia, defined as the angle formed between the bicondylar axis of the proximal tibia and the bimalleolar axis, is an indicator of tibial torsion. This angle has been previously investigated by various means: clinical assessment only [1,2,4-6,9,10,20,21], radiographic examination [1,5,10,22,23], ultrasound [3,[24][25][26][27], and CT scan [18,21,24,28,29]. According to those studies, the torsion angle of the tibia varies in normal individuals from neutral at birth to a value from 17.41 to 40.51 of external torsion at maturity.…”
Section: Discussionmentioning
confidence: 99%